Corporate Social Responsibility For Disability Employment Protection In Indonesia - Adinda Agnes Sahila; Oxtavia Fafirotun Nasikhah; Risya Syifa Wicahyoko; Ilhamu Yaa Habibi (Universitas Negeri Surabaya, 2025)
The fulfillment of the right to work for persons with disabilities remains a significant legal issue in Indonesia despite the existence of regulatory frameworks guaranteeing equal employment opportunities. From a disability rights perspective, the right to work constitutes a fundamental component of human dignity and equality. However, the implementation of such rights remains limited due to structural barriers, discrimination, and weak enforcement of legal obligations. This study adopts a human rights-based approach to analyze the role of Corporate Social Responsibility (CSR) in supporting disability employment rights and strengthening inclusive legal protection. The research aims to examine the legal regulation of CSR obligations and to assess their potential integration into disability-inclusive employment policies in Indonesia. This research uses normative legal methods with statutory and conceptual approaches. The findings indicate that although Indonesia has established a relatively comprehensive legal framework, there is a lack of explicit integration between CSR obligations and disability employment protection. This reflects a gap in inclusive legal protection mechanisms. Therefore, this study highlights the need to reposition CSR as a binding legal responsibility aligned with human rights principles, in order to strengthen inclusive employment systems for persons with disabilities.